PENGARUH PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI SMAN 5 PARIAMAN - Astari, Mila (Jurnal Edukasi dan Penelitian Matematika, 2024)
The final results of students' mathematics learning can be observed in their learning results. Even so, the learning outcomes of class XI students at SMA N 5 Pariaman are still relatively low. The application of the problem posing model is a strategy to try to improve student learning outcomes. The aim of the research is to identify and characterize whether the learning outcomes obtained from the Problem Posing Learning Model are superior to the learning outcomes obtained from the Direct Learning Model. The type of research used was quasi-experimental with a Randomized Control Group Only Design. The research population was class XI students at SMAN 5 Pariaman for the 2023/2024 academic year. Samples were obtained using a random sampling approach. The experimental group is in class XI.F1 and the control class is in class XI.F3. The final test serves as the tool. T-test analysis was performed on the data. The learning outcomes using the problem posing model at SMAN 5 Pariaman are more effective than the learning outcomes using the direct learning model,, according to the analysis of the final exam results, which yielded a P-Value> 0.05 for the hypothesis test.Keywords – Problem posing Learning Model, Learning Outcomes